Towards Active Software Engineering Ontology - Pakdeetrakulwong, Udsanee; Wongthongtham, Pornpit (IEEE, 2013)
Due to the globalization of software development and for a number of business reasons, software companies have adopted the global software development approach that enables project team members to work across multiple sites. While on the one hand, a globally dispersed project offers several advantages, on the other hand, it creates additional challenges in regard to communication, coordination and information sharing. In order to address such challenges, in the literature, the software engineering ontology has been developed to provide a common understanding of software engineering domain knowledge and share software project information among dispersed team members. However, the nature of the software engineering ontology is still passive as is the nature of many existing ontologies. Passive means that users of the ontology need the competence to access and translate what they are looking for into the concepts and relations defined in it; otherwise, they may not be able to receive precise knowledge and project information.The purpose of this paper is to develop a methodology to provide active support to access and recommend knowledge and project information in the software engineering ontology. Two main key technologies, i.e., agent-based system and recommendation techniques are exploited in this research. Intelligent agents can cope with the distribution and interoperability of a global software development environment and when they are integrated with recommendation approaches, they can offer automated suggestions to actively support software team members. This aims at providing the most relevant and precise situational knowledge and will lead to improving the effectiveness of communication and coordination of long-distance collaborative work. The scope of the proposed work is not just limited to software engineering ontology; rather, it is domain-independent and can be applied to any other ontology in any domain.